Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Tetracene Ultrathin Film Growth on Hydrogen-Passivated Silicon - Niederhausen, Jens; MacQueen, Rowan W.; Lips, Klaus; Aldahhak, Hazem; Schmidt, Wolf Gero; Gerstmann, Uwe (Langmuir)

Photochemical Ring Opening of Oxirane Modeled by Constrained Density Functional Theory - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (ACS Omega)

Carrier-wave population transfer in semiconductors - Zuo, R; Song, X; Meier, Torsten; Yang, W (Journal of Physics: Conference Series)

Investigation of influencing parameters on the joint formation of the self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Lechner, Michael; Bobbert, Mathias; Meschut, Gerson; Merklein, Marion

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

罗铮 译.“大数据资本主义时代的马克思（Karl Marx in the Age of Big Data Capitalism) - Fuchs, Christian (世界社会主义研究年鉴 (World Socialism Research Yearbook 2020))

罗铮 译.“大数据资本主义时代的马克思（Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (国外理论动态（Foreign Theoretical Trends) 2020 (4))

Preface to Manfred Knoche’s Article “Science Communication and Open Access: The Critique of the Political Economy of Capitalist Academic Publishers as Ideology Critique” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cellulose Nanocrystal-Templated Tin Dioxide Thin Films for Gas Sensing - Ivanova, Alesja; Frka-Petesic, Bruno; Paul, Andrej; Wagner, Thorsten; Jumabekov, Askhat N.; Vilk, Yury; Weber, Johannes; Schmedt auf der Günne, Jörn; Vignolini, Silvia; Tiemann, Michael; Fattakhova-Rohlfing, Dina; Bein, Thomas (ACS Applied Materials & Interfaces)
Porous tin dioxide is an important low-cost semiconductor applied in electronics, gas sensors, and biosensors. Here, we present a versatile template-assisted synthesis of nanostructured tin dioxide thin films using cellulose nanocrystals (CNCs). We demonstrate that the structural features of CNC-templated tin dioxide films strongly depend on the precursor composition. The precursor properties were studied by using low-temperature nuclear magnetic resonance spectroscopy of tin tetrachloride in solution. We demonstrate that it is possible to optimize the precursor conditions to obtain homogeneous precursor mixtures and therefore highly porous thin films with pore dimensions in the range of 10–20 nm (ABET = 46–64 m2 g–1, measured on powder). Finally, by exploiting the high surface area of the material, we developed a resistive gas sensor based on CNC-templated tin dioxide. The sensor shows high sensitivity to carbon monoxide (CO) in ppm concentrations and low cross-sensitivity to humidity. Most importantly, the sensing kinetics are remarkably fast; both the response to the analyte gas and the signal decay after gas exposure occur within a few seconds, faster than in standard SnO2-based CO sensors. This is attributed to the high gas accessibility of the very thin porous film.

Nanoporous aluminum oxide micropatterns prepared by hydrogel templating - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanotechnology)
Micropatterned nanoporous aluminum oxide arrays are prepared on silicon wafer substrates by using photopolymerized poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel micropatterns are fabricated by spreading the prepolymer mixture on the substrate, followed by UV photopolymerization through a micropatterned mask. The hydrogel is covalently bonded to the substrate surface. Al2O3 is produced by swelling the hydrogel in a saturated aluminum nitrate solution and subsequent thermal conversion/calcination. As a result, micropatterned porous Al2O3 microdots with heights in µm range and large specific surface areas up to 274 m2 g−1 are obtained. Hence, the hydrogel fulfills a dual templating function, namely micropatterning and nanoporosity generation. The impact of varying the photopolymerization time on the properties of the products is studied. Samples are characterized by light and confocal laser scanning microscopy, scanning electron microscopy, energy-dispersive x-ray spectrometry, and Kr physisorption analysis.

Synthesis of Metal Oxide Inverse Opals from Metal Nitrates by PMMA Colloidal Crystal Templating - Zhang, Xuyang; Weinberger, Christian; Amrehn, Sabrina; Wu, Xia; Tiemann, Michael; Wagner, Thorsten (European Journal of Inorganic Chemistry)
Metal oxide inverse opals are interesting for various applications. To achieve highly ordered inverse opal structures, one important issue during the colloidal crystal templating procedure is to form a stable precursor network before the template loses its structural integrity at high temperature. Using poly(methyl methacrylate), PMMA, colloidal crystal templates, it is essential to consider the physical and chemical changes of the precursors induced by the changes of PMMA during the thermal conversion. For a systematic investigation of this matter, we synthesized a variety of metal oxide inverse opals from the respective metal nitrates, including Cr2O3, Ga2O3, Fe2O3, In2O3, CuO, CeO2, and ZnO, to compare the effect of various modifications of precursors on the structural and optical properties. When the nitrate precursors have a lower thermal stability than the PMMA template, we have modified the metal nitrates by chelating or by polyacrylamide gelation to form more stable precursor networks.

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Functional Nanoporous Materials - Weinberger, Christian; Tiemann, Michael (Nanomaterials)
This Special Issue on “Functional Nanoporous Materials” in the MDPI journal nanomaterials features seven original papers ...

Kleider in Bewegung. Frauenmode seit 1850 - Kraft, Kerstin

Water-based primary cell for powering of wireless sensors - Petrov, Dmitry; Hilleringmann, Ulrich (2020 IEEE SENSORS)

Musikwissenschaft und Theologie im Dialog - Johann Sebastian Bachs "h-Moll-Messe" und "Johannes-Passion"
Die h-Moll-Messe und die Johannes-Passion sind unzweifelhaft zwei Hauptwerke Johann Sebastian Bachs. Der vorliegende Band versammelt die Vorträge aus zwei Symposien, die im Oktober 2017 und März 2019 in Essen abgehalten worden sind. Im Dialog zwischen Theologie und Musikwissenschaft werden in den Beiträgen unterschiedliche Aspekte fokussiert, die je nach Werk zum einen eher auf dem Gebiet der Genese, Rezeption und Edition (h-Moll-Messe), zum anderen eher auf dessen theologischem oder musikgeschichtlichem Kontext (Johannes-Passion) liegen. In dieser interdisziplinären Zusammenstellung werden zahlreiche neue Facetten der Werke und ihrer Kontexte erhellt.

Die h-Moll-Messe szenisch: Rosamund Gilmore (1986), Achim Freyer (1996) und Jochen Biganzoli (2017) - Höink, Dominik (Musikwissenschaft und Theologie im Dialog - Johann Sebastian Bachs "h-Moll-Messe" und "Johannes-Passion")

Zur Stabilisierung medienbezogener Handlungsroutinen im Lehrer*innenberuf. Längsschnittliche Betrachtungen zur Integration von Tablets in den Arbeitsalltag - Dehmel, Lukas; Gerhardts, Lara; Meister, Dorothee M. (Mobile Medien im Schulkontext)

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Shnayien, Marie-Luise

Explorations in Digital Cultures

Reparaturbetrieb, Inklusion und Fachkräftesicherung Transformation der Benachteiligtenförderung in Deutschland. - Heisler, Dietmar (Historische Berufsbildungsforschung Perspektiven auf Wissenschaftsgenese und -dynamik.)
Jeder Wissenschaftsdisziplin hilft ein Bewusstsein ihrer Geschichte und die Kenntnis ihrer Vielfalt, Paradigmen und Entwicklungsmöglichkeiten. Darauf basierend können Forschende ihr spezifisches Potential, Wissen und Handlungsrepertoire entfalten. Dabei ist Geschichtsschreibung und historische Berufsbildungsforschung immer zugleich selbst gefangen in ihrer je eigenen Zeit, beschränkt durch die Perspektiven der Personen, die sich an dem Rückblick beteiligen. Das macht Geschichte auch immer zur Geschichte der Herrschenden, die eine spezifische Perspektive und die mit ihr verbundene Forschung schreibend tradieren. Deshalb ist Vielfalt für die historische Berufsbildungsforschung so wertvoll, weil sie sich gegen verengte, eindimensionale Retrospektive stellt, gewissermaßen in die Ritzen und Fugen der Zeit schauen lässt. Basierend auf einer Tagung der Herausgeber im September 2019 zu „Retrospektiven, Perspektiven & Synergien einer Historischen Berufsbildungs- und Wissenschaftsforschung" an der Universität Rostock, entfaltet sich die Bandbreite der historischen Berufsbildungsforschung. Der Band vereint paradigmatische, mal stärker biografischen Zugänge sowie systemisch-gesellschaftspolitische und schließlich Analysen zur Genese der Wissenschaftsdisziplin. In den Beiträgen wird dem Einfluss von Einzelpersönlichkeiten und Forschungsparadigmen ebenso wie dem von Bildungssystemen am Beispiel der DDR, Skandinaviens und der bundesdeutschen Bildungspolitik nachgegangen. Vereint sind sowohl Beiträge zur Entstehung der Berufs- und Wirtschaftspädagogik, zur Rekonstruktion der Benachteiligtenförderung, Soziökonomie, Pflegedidaktik und Frauenforschung als auch Analysen berufsspezifischer Betrachtungen am Beispiel des Druckgewerbes, der Offiziere und der Ausbilder*innen.
Keywords: Benachteiligtenförderung; historische Berufsbildungsforschung; berufliche Förderung; Sozialpädagogik

(Un)Sicherheitsproduktion im Cyberspace. Cybersecurity-Architekturen in Deutschland und der Schweiz - Hälterlein, Jens (TATuP)

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen und der Stellenwert einer Fachlichkeitskonzeption von Lehrenden der Fächergruppe Erziehungswissenschaft - Engemann, Mario

Gero Fuchs: Gewinn als Umbruch der Ordnung? Der Fall des Siegburger Töpfers Peter Knütgen im 16. Jahrhundert, Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Laura Schmidt: Weihnachtliches Theater. Zur Entstehung und Geschichte einer bürgerlichen Fest- und Theaterkultur, Bielefeld 2017 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Inklusion und Intersektionalität im Kontext frühkindlicher Medienbildungsforschung. Sprachkulturelle Homogenität und Diversität sowie ihre Auswirkungen auf pädagogische Kommunikation in der Frühen Bildung - Günesli, Habib (QfI - Qualifizierung für Inklusion Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Dieser Beitrag basiert auf den Ergebnissen eines im Jahr 2019 abgeschlossenen Promotionsvorhabens im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang zu den Mediensozialisationsbedingungen von deutschen, deutsch-türkischen und deutsch-anderen vier und fünf Jahre alten Mädchen und Jungen in den sozialen Feldern Familie und Kita. Im vorliegenden Beitrag wird auf die Befragung der ErzieherInnen fokussiert, die mittels halbstandardisierter Fragebögen durchgeführt wurde. Untersucht wurde, wie sich der sprachlich-kulturelle Hintergrund der Kinder für das Kommunikationsverhalten der ErzieherInnen mit den Kindern in pädagogischer Anschlusskommunikation und in Gesprächen mit den Eltern der Kinder auswirkt. Hier wurde auch eine intersektionale Perspektive eingenommen und parallel zur Herkunftskultur auch das biologische Geschlecht der Kinder in die Auswertung einbezogen. Es stellte sich heraus, dass die Kommunikation sowohl mit den Kindern als auch mit den Eltern in Abhängigkeit der Herkunftskultur der Kinder und auch ihres Geschlechtes erfolgt. Pädagogisch ist zu fragen, inwiefern es den pädagogischen Fachkräften gelingt, benachteiligende Ausgangslagen auch tatsächlich auszugleichen und Partizipation im Sinne von Inklusion zu ermöglichen. Ausgehend von diesen Ergebnissen wird in diesem Beitrag die Bedeutung und Relevanz der Überschneidungen und Interdependenzen von Ungleichheitsdimensionen für eine inklusionsorientierte Qualifikation pädagogischer Fachkräfte in institutionell-frühkindlichen Medienbildungskontexten diskutiert. Konkret richtet sich der Blick auf die sprachlich-kulturelle Ein- und Vielfalt in den frühkindlichen Einrichtungen sowie die Wahrnehmungen und Einschätzungen der pädagogischen Fachkräfte, die sie in Hinblick auf die Kooperationswilligkeit der Eltern, die Anschlusskommunikation mit den Kindern und schließlich die medialen Fähig- und Fertigkeiten der Kinder äußern.

Regularizing neural networks with gradient monitoring - Chadha, Gavneet Singh; Meydani, Elnaz; Schwung, Andreas (Recent Advances in Big Data and Deep Learning: Proceedings of the INNS Big Data and Deep Learning Conference INNSBDDL2019, held at Sestri Levante, Genova, Italy 16-18 April 2019)

Probing nonclassicality with matrices of phase-space distributions - Bohmann, Martin; Agudelo, Elizabeth; Sperling, Jan (Quantum)
We devise a method to certify nonclassical features via correlations of phase-space distributions by unifying the notions of quasiprobabilities and matrices of correlation functions. Our approach complements and extends recent results that were based on Chebyshev's integral inequality \cite{BA19}. The method developed here correlates arbitrary phase-space functions at arbitrary points in phase space, including multimode scenarios and higher-order correlations. Furthermore, our approach provides necessary and sufficient nonclassicality criteria, applies to phase-space functions beyond s-parametrized ones, and is accessible in experiments. To demonstrate the power of our technique, the quantum characteristics of discrete- and continuous-variable, single- and multimode, as well as pure and mixed states are certified only employing second-order correlations and Husimi functions, which always resemble a classical probability distribution. Moreover, nonlinear generalizations of our approach are studied. Therefore, a versatile and broadly applicable framework is devised to uncover quantum properties in terms of matrices of phase-space distributions.

Classical evolution in quantum systems - Sperling, Jan; Walmsley, I A (Physica Scripta)

Transfer function replacement of phenomenological single-mode equations in semiconductor microcavity modeling - Carcamo, M.; Schumacher, Stefan; Binder, R. (Applied Optics)
Semiconductor microcavities are frequently studied in the context of semiconductor lasers and in application-oriented fundamental research on topics such as linear and nonlinear polariton systems, polariton lasers, polariton pattern formation, and polaritonic Bose–Einstein condensates. A commonly used approach to describe theoretical properties includes a phenomenological single-mode equation that complements the equation for the nonlinear optical response (interband polarization) of the semiconductor. Here, we show how to replace the single-mode equation by a fully predictive transfer function method that, in contrast to the single-mode equation, accounts for propagation, retardation, and pulse-filtering effects of the incident light field traversing the distributed Bragg reflector (DBR) mirrors, without substantially increasing the numerical complexity of the solution. As examples, we use cavities containing GaAs quantum wells and transition-metal dichalcogenides (TMDs).
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

Realization of all-optical vortex switching in exciton-polariton condensates - Meier, Torsten; Ma, Xuekai; Berger, Bernd; Aßmann, Marc; Driben, Rodislav; Schneider, Christian; Höfling, Sven; Schumacher, Stefan (Nature communications)
Vortices are topological objects representing the circular motion of a fluid. With their additional degree of freedom, the vorticity, they have been widely investigated in many physical systems and different materials for fundamental interest and for applications in data storage and information processing. Vortices have also been observed in non-equilibrium exciton-polariton condensates in planar semiconductor microcavities. There they appear spontaneously or can be created and pinned in space using ring-shaped optical excitation profiles. However, using the vortex state for information processing not only requires creation of a vortex but also efficient control over the vortex after its creation. Here we demonstrate a simple approach to control and switch a localized polariton vortex between opposite states. In our scheme, both the optical control of vorticity and its detection through the orbital angular momentum of the emitted light are implemented in a robust and practical manner.

k.p-based multiband simulations of non-degenerate two-photon absorption in bulk GaAs - Hannes, Wolf-Rüdiger; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIV)

Strongly nonresonant four-wave mixing in semiconductors - Hannes, W.-R.; Trautmann, Alexander; Stein, M.; Schäfer, F.; Koch, M.; Meier, Torsten (Physical Review B)

Enhanced high-order harmonic generation in semiconductors by excitation with multicolor pulses - Song, Xiaohong; Yang, Shidong; Zuo, Ruixin; Meier, Torsten; Yang, Weifeng (Physical Review A)

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Generationelle und gesellschaftliche Differenzen im wiedervereinigten Deutschland - "Der neunzigste Geburtstag. Ein ländliches Idyll" von Günter de Bruyn in postkolonialer Lesart. - Müller, Inez

Transmediale und transkulturelle Schreibweisen im Exil der Gegenwart - Prosa und Lyrik syrischer Autoren in Europa - Müller, Inez (Peter Weiss Jahrbuch)

The Influence of Hydrothermal Aging on the Material Properties of Continuous Fiber-Reinforced Thermoplastics and its Non-Destructive Characterization - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Advances in Polymer Processing 2020)

Modeling and Optimization of Rectangular Latent Heat Storage Elements in an Air-Guided Heat Storage System - Grabo, Matti; Staggenborg, Christoph; Philippi, Kai Alexander; Kenig, Eugeny (Frontiers in Energy Research)

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Morbach, A.; Neukötter, Moritz; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
The influence of latent heat storage elements on the cooling performance and the temperature rise time of household refrigerating appliances is studied experimentally in the context of the “new global refriger- ator standard”IEC 62552:2015. In addition to the daily energy consumption, this international standard- ization introduced performance tests for cooling capacity and temperature rise time. While the cooling capacity has long been anchored in various test procedures of consumer organizations, the temperature rise time, which has only been tested on freezers so far, will be a decisive factor in the future. Moreover, the need for so-called "smart appliances" that may balance power consumption is increasing since such devices may compensate the volatility of renewable energies and thus stabilize the power grid. Against this background, eight commercial household refrigerators and refrigerator-freezers are equipped with polymer-bound phase change materials (PCM) and their performance is determined under the new stan- dard test conditions. The results show that the introduction of PCM increases the cooling capacity by up to 33 % and also increases the temperature rise time by up to 145 %, without affecting power consump- tion, as compared to the unmodified refrigeration appliances.

Age-related efficiency loss of household refrigeration appliances: Development of an approach to measure the degradation of insulation properties - Hueppe, Christian; Geppert, Jasmin; Stamminger, Rainer; Wagner, Hendrik; Hoelscher, Heike; Vrabec, Jadran; Paul, Andreas; Elsner, Andreas; Becker, Wolfgang; Gries, Ulrich; Freiberger, Alfred (Applied Thermal Engineering)
Despite the omnipresence of household refrigeration appliances, there is still a lack of knowledge about their agerelated efficiency loss over time. Past studies provide basic evidence for increasing electricity consumption of cooling appliances with ageing but fail to investigate the associated technical wear. Concentrating on the degradation of the thermal insulation, we first determined the ageing process of sealed samples of polyurethane rigid foam by investigating changes in cell gas composition and thermal conductivity over time. Simultaneously, the main challenge was to develop an approach that investigates the age-related efficiency loss of the insulation without its destruction. This testing procedure is referred to as the Bonn method. The non-destructive Bonn method was applied to varying refrigerator models in a series of successive experiments to evaluate the insulation degradation over time. Subsequently, the physical relationship between the test value of the Bonn method and the heat transfer through the multi-layered compartment walls of domestic refrigeration appliances was established, ultimately characterising the degrading insulation in terms of increasing heat transfer. Our results give substantiated evidence that the efficiency loss of cooling appliances is greatly influenced by insulation degradation over time. The ageing of sealed samples of polyurethane rigid foam indicates a large initial increase of thermal conductivity by 15% within the first year, corresponding to a change in cell gas composition. These results are in line with those of the Bonn method, emphasising an increasing heat flow through the multi-layered compartment walls of domestic refrigerators with ageing. Therewith, the present study is of significance to a wide range of stakeholders and forms the basis for future research.